Sovereign risk and economic complexity - José Eduardo Gómez González; Jorge Uribe; Oscar M. Valencia (Inter-American Development Bank (IDB), 2024)
This paper investigates how a country's economic complexity influences its sovereign yield spread with respect to the United States. Notably, a one-unit increase in the Economic Complexity Index is associated with a reduction of about 87 basis points in the 10-year yield spread. However, this effect is largely non-significant for maturities under three years. This suggests that economic complexity affects not only the level of the sovereign yield spreads but also the curve slope. The first set of models utilizes advanced causal machine learning tools, while the second focuses on economic complexity's predictive power. Economic complexity ranks among the top three predictors, alongside inflation and institutional factors like the rule of law. The paper also discusses the potential mechanisms through which economic complexity reduces sovereign risk and emphasizes its role as a long-run determinant of productivity, output, and income stability, and the likelihood of fiscal crises.
Keywords: F34; G12; G15; H63; O40; 330; convenience yields; double-machine-learning; government debt; sovereign credit risk; XGBoost; yield curve